Perancangan Sudut Panel Surya Untuk Sistem Solar Tracker Di Kabupaten Karawang Menggunakan Metode Simulasi PVsyst - Alam, Kaizar Nur; Santoso, Dian Budhi; Rahmadewi, Rani (Fakultas Teknik UMSU, 2023)
The use of solar panel systems as solar energy utilization has become an attractive solution in order to reduce the use of fossil energy for electricity conversion raw materials. A solar Tracker system is used to increase the efficiency of solar panels by facing the solar panels to the angle of incidence of sunlight. This research aims to design the optimum angle that will be applied to the solar tracker system at University of Singaperbangsa Karawang. This study uses the simulation method of PVsyst software to analyze the performance of solar panel systems at various variations of tilt angle and azimuth. This research involves two optimum angle variations (5° and 9°), as well as an azimuth direction of 0° (system facing North) that will be applied to a static solar panel system and a solar tracker system. The collected sunlight data was inputted from the Meteonorm 8.0 database. The results of this study inform that the solar tracker system (Tilt Angel 5°) gets the most optimal energy compared to the other three systems, with the energy produced amounting to 247.92 kWh / year, and gets the smallest percentage of lost energy which is 7.46%. Following up on this research, it is necessary to combine research methods to determine the exact position of the Tilt Angel and Azimuth, then direct application is needed to compare the accuracy of the data obtained from the simulation.